2016
DOI: 10.1016/j.invent.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Information quality and dynamics of patients' interactions on tonsillectomy web resources

Abstract: Information technologies have drastically altered the way patients gather health-related information. By analysing web resources on tonsillectomy, we expose information quality and dynamics of patients' interactions in the online continuum. Readability was assessed using Flesch Reading Ease (FRE), Flesch Kincaid Grade Level (FKGL), Simple Measure of Gobbledygook (SMOG), and Gunning Fog Index (GFI). Comprehensibility and actionability were assessed using the Patient Education Materials Assessment Tool (PEMAT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
3
0
4
Order By: Relevance
“…Prior studies across multiple specialties have evaluated both POEMs and A/V education materials and have found that patient education materials online are often incorrect and/or incomprehensible . The PEMAT specifically has been used most frequently to evaluate and study educational materials in internal medicine literature.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies across multiple specialties have evaluated both POEMs and A/V education materials and have found that patient education materials online are often incorrect and/or incomprehensible . The PEMAT specifically has been used most frequently to evaluate and study educational materials in internal medicine literature.…”
Section: Discussionmentioning
confidence: 99%
“…(23,30) Since information is often poorly moderated, there is a risk of spreading potentially harmful information via the Internet. (31) Coupled with the wide use of the Internet as an initial or only primary source of health-related information, there is a great risk for patients and carers. Furthermore, given that health literacy is relatively low in the general population, (8,9) patients (or their carers) may: fail to recognise that important information is missing, fail to acknowledge biased content, misinterpret some medical information, and/or be unable to recognise non-evidence-based material.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has examined the IRR of the two PEMAT domains of understandability and actionability. These studies found that there was no significant difference between the PEMAT scores of two raters on webpages on tonsillectomy [25] or maritime health related information [26] at the p < 0.05 level. In addition, evaluations of patient education materials on c. Diff and surgical site infections had kappa values of 0.80 when comparing understandability and actionability scores among 3 raters [13, 14].…”
Section: Discussionmentioning
confidence: 99%